Ultrafast static and diffusion-controlled electron transfer at Ag29 nanocluster/molecular acceptor interfaces. Issue 10 (9th November 2015) - Aly, Shawkat M.; AbdulHalim, Lina G.; Besong, Tabot M. D.; Soldan, Giada; Bakr, Osman M.; Mohammed, Omar F.
Abstract : We quantitatively separate the contributions of static and collision-caused photo-induced electron transfer from Ag29 NC clusters to MV 2+ through both transient absorption and time-resolved fluorescence experiments. Abstract : Efficient absorption of visible light and a long-lived excited state lifetime of silver nanoclusters (Ag29 NCs) are integral properties for these new clusters to serve as light-harvesting materials. Upon optical excitation, electron injection at Ag29 NC/methyl viologen (MV 2+ ) interfaces is very efficient and ultrafast. Interestingly, our femto- and nanosecond time-resolved results demonstrate clearly that both dynamic and static electron transfer mechanisms are involved in photoluminescence quenching of Ag29 NCs.